The complete women’s psychotherapy treatment planner - Ancis, Julie R. (John Wiley & Sons, 2007)
Incorporating the new American Psychological Association Guidelines for Psychological Practice with Girls and Women, The Complete Women's Psychotherapy Treatment Planner provides all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payors, and state and federal agencies.